2021
DOI: 10.1016/j.onehlt.2021.100216
|View full text |Cite
|
Sign up to set email alerts
|

Animals as potential reservoirs for dengue transmission: A systematic review

Abstract: Dengue is a rapidly spreading mosquito-borne flavivirus infection that is prevalent in tropical and sub-tropical regions. Humans are known to be the main reservoir host maintaining the epidemic cycles of dengue but it is unclear if dengue virus is also maintained in a similar enzootic cycle. The systematic review was conducted in accordance to Cochrane's PRISMA recommendations. A search was done on PubMed, EMBASE, Scopus and Cochrane Library. Key data on animal dengue positivity was extracted and classified ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 82 publications
0
24
1
Order By: Relevance
“…Clearly, the African continent as a whole is severely under-sampled in the context of DENV and other arboviruses [ 20 ]. Indeed, it is possible that viruses of these ancestral lineages and clusters may be circulating unnoticed in the human populations and/or in sylvatic reservoirs [ 7 , 46 ], as has been observed for DENV2 in Senegal [ [47] , [48] , [49] ]. In the present study, two sequences isolated almost 30 years apart in Senegal were identified as genetically closely related in the DENV4 phylogeny (cluster I, Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clearly, the African continent as a whole is severely under-sampled in the context of DENV and other arboviruses [ 20 ]. Indeed, it is possible that viruses of these ancestral lineages and clusters may be circulating unnoticed in the human populations and/or in sylvatic reservoirs [ 7 , 46 ], as has been observed for DENV2 in Senegal [ [47] , [48] , [49] ]. In the present study, two sequences isolated almost 30 years apart in Senegal were identified as genetically closely related in the DENV4 phylogeny (cluster I, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…2 ), may be of significance for our understanding of future dengue virus epidemiology in Africa, perhaps directly indicating that DENV does survive long-term in the sylvatic forest environment. Thus, to understand the epidemiology of DENV, one must apply a One Health approach to examine the environmental characteristics that promote suitable living-conditions for the mosquito-vector and its interaction with animal reservoirs and endemic transmission to humans [ 7 ]. Historically, it has been believed for many years that people of African ethnicity may be more resistant than Asians and Europeans, to infection by dengue viruses and this was recently supported by studies of dengue fever, in Colombia [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, WNV migration from the Eastern United States to the West Coast by 2003 was undoubtedly due to infection and persistence of this virus in migratory birds, reptiles, and amphibians [ 31 ]. In addition to non-human primates, dengue infection has occurred in pigs, marsupials, bats, birds, horses, bovids, rodents, and canines [ 32 , 33 ]. There is potential enzootic transmission, but regular dengue virus spillback cannot be excluded.…”
Section: Infection and Persistence Of Flaviviruses In Wildlifementioning
confidence: 99%
“…Research suggests that the principal reservoirs of mosquito-borne flaviviruses are non-human primates and avian species, often referred to as a “sylvatic cycle” [ 32 , 55 ]. Additional mammals generally serve as accidental hosts, but not always, as this still requires additional research [ 10 ].…”
Section: Infection and Persistence Of Flaviviruses In Wildlifementioning
confidence: 99%